L’Histoire de l’Espagne à l’épreuve du musée. Les expériences du Museo Nacional Centro de Arte Reina Sofía (2008-2023) - Nicolas Morales (Amnis)
Between 2008 and 2023, the Museo Nacional Centro de Arte Contemporáneo Reina Sofía in Madrid, under the direction of Manuel Borja-Villel, sought to challenge a type of public representation of history that was mainly in place during the Spanish democratic transition. Promoting a historicising vision of the collection that was out of step with the previous directors who had succeeded one another since the museum's creation in 1988-1990, the Borja-Villel team drew on the historiographical currents emerging at the end of the 1990s and sought to make visible historical aesthetic movements from the countries of the South, mainly Latin America, often associated with Marxist-inspired social movements that had traditionally been marginalised by critics and the museum establishment. Inspired by the theories of Chantal Mouffe, this approach aimed to make visible radical artistic practices that had been annihilated by a consensualist transitional discourse. The analysis of one of the major historical exhibitions of its mandate, Campo Cerrado. Arte y poder en la posguerra española. 1939-1953, by art historian María Dolores Jiménez-Blanco, shows how the museum institution ‘makes and breaks’ the public representation of Spain's contemporary history. The aim is to measure the tangible limits of this approach and, above all, the current difficulty in extricating ourselves from a narrative inherited from Franco's historiography and reassumed during the democratic transition.